The Influence of Age Diversity on Organizational Identification - Łucja Waligóra (Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu, 2025)
Aim: The aim of this study was to determine the role of employee age heterogeneity in building a sense of belonging to the organization and to recognize the impact of human resource management activities and an inclusive climate on this relationship.